Peningkatan Motivasi Hasil Belajar Ekonomi Melalui Model Pembelajaran Student Centered Learning - Mastufah, Mastufah (Attractive : Innovative Education Journal, 2019)
In the process of learning Economics (Accounting) required a certain strategy and strong motivation. Teachers play a very important role, especially in terms of designing learning scenarios. Teachers should be able to choose a learning model that can increase the motivation of learners, in accordance with the characteristics of subjects, and characteristics of learners so that learning can take place optimally. The aim of this classroom action research is to improve the learning of learners using the student centered learning model. This research was conducted in class XI IPS1, MAN 1 Cilegon semester 1, material Posting from Juku Kebuku Besar Journals, post to a subsidiary "using cycles, in this study the author tries to 2 cycles. The results show that in each cycle of understanding the accounting, cycle of a merchandising company on post material from a special journal to the ledger, posting to the auxiliary book, gained increased motivation and learning outcomes. In general it can be concluded that the use of student centered learning model can improve the motivation and learning outcomes of learners. Key words: Student Centered Learning Model, Learn Economics Accounting